2020
DOI: 10.3390/ijms21051708
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Synaptic and Cellular Ultrastructure in Neurons Differentiated from Human Induced Neural Stem Cells—An Optimized Protocol

Abstract: The size of the synaptic subcomponents falls below the limits of visible light microscopy. Despite new developments in advanced microscopy techniques, the resolution of transmission electron microscopy (TEM) remains unsurpassed. The requirements of tissue preservation are very high, and human post mortem material often does not offer adequate quality. However, new reprogramming techniques that generate human neurons in vitro provide samples that can easily fulfill these requirements. The objective of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…A different explanation could lie in our very conservative approach: we only included synapses if at least two out of three independent researchers agreed that they were clearly visible. Moreover, the enhanced osmium staining protocol (Deerinck et al, 2010) applied here has been shown to stain certain proteinaceous structures like the mammal postsynaptic density less intensely than previous protocols (Capetian et al, 2020), so some presynaptic bars may have been excluded because of insufficient staining. This is a possibility, as when TEM methods with standard contrasting were used in L1 and L4 RS were abundant in the LGMDs (figure 9 in Simmons et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…A different explanation could lie in our very conservative approach: we only included synapses if at least two out of three independent researchers agreed that they were clearly visible. Moreover, the enhanced osmium staining protocol (Deerinck et al, 2010) applied here has been shown to stain certain proteinaceous structures like the mammal postsynaptic density less intensely than previous protocols (Capetian et al, 2020), so some presynaptic bars may have been excluded because of insufficient staining. This is a possibility, as when TEM methods with standard contrasting were used in L1 and L4 RS were abundant in the LGMDs (figure 9 in Simmons et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…At the periphery of the neuroepithelial rosettes, different cell types in organoids and BBB-organoids are detected by ultrastructural studies. Figure 4 shows neural-like cells [21,22] with a voluminous nucleus and axon-like extensions (Figure 4, “n” in inserts a5 and b5), and round cells with scarce cytoplasm and no clear extension, usually coupled with neurites (Figure 4, inserts a4, b4), a morphology which is indicative of a glial phenotype. In addition, groups of neurites with microtubules and core-dense vesicles can be observed (Figure 4, boxed regions in inserts a2 and b2, enlarged views in a3 and b3).…”
Section: Resultsmentioning
confidence: 99%
“…Conventional TEM sample preparation can induce artefacts due to protein aggregation or cross-linking which reportedly disrupts cellular ultrastructure. Notably, subcellular organelles in cells were shown to lose integrity following standard glutaraldehyde and formaldehyde-based fixation [28]. Therefore, we examined whether high-pressure freezing and freeze-substitution was better at preserving the ultrastructure of cellular organelles.…”
Section: Cryogenic Sample Preparation Preserves Mitochondrial Ultrast...mentioning
confidence: 99%
“…These methods can lead to artefacts and distorted cellular membranes and organelles, including mitochondria [22]. Importantly, neuronal cells are particularly fragile cells and thus more vulnerable to damage during preprocessing using these standard techniques [27,28]. Secondly, TEM has often been employed as a qualitative rather than quantitative measurement of morphology.…”
Section: Introductionmentioning
confidence: 99%